Exploring the impact of short daily haemodialysis on muscle strength and bone health in end‐stage kidney disease patients - Fernanda Silveira Tavares; Hugo deLuca Corrêa; Kenneth R. Wilund; Lysleine Alves Deus; Thais Branquinho deAraújo; Carmen Tzanno‐Martins; Vitória Marra daMotta Vilalva Mestrinho; Rafael Lavarini dosSantos; Andrea Lucena Reis; Fernando Honorato Souza; Luiz Roberto deSousa Ulisses; Helen Souto Siqueira Cardoso; et al. (Wiley, 2024)
Abstract Background Short‐daily haemodialysis (SDH) has been strongly recommended over conventional haemodialysis (CHD) for end‐stage kidney disease patients, though few studies have directly compared the effects of these two haemodialysis (HD) modalities on clinical variables related to patient's health. Methods We conducted a cross‐sectional study in individuals undergoing HD, comparing epidemiological, clinical, metabolic, inflammatory, anthropometric, bone health/metabolism, and skeletal muscle function according to dialysis modality. One‐hundred seventy‐eight patients (20.8% females, 62 ± 2.5 years old), were analysed in this study, 86 (48%) of whom were undergoing CHD versus 92 (51%) who were undergoing SDH. Results SDH patients had significantly higher serum albumin levels (3.93 vs. 3.66 g/dL, P < 0.0001) and higher Kt/v (2.6 vs. 2.38, P < 0.0001). SDH group presented a significantly lower number of erythropoietin‐stimulating agents compared with CHD group (percentage: 53.3 vs. 83.7%, P < 0.0001) and had lower levels of serum phosphate (4.9 vs. 5.3 mg/dL, P = 0.004) and parathyroid hormone (PTH) (398.4 vs. 480.4 pg/mL, P < 0.001) compared with CHD patients. In terms of bone health and metabolism, SDH patients had significantly higher total BMD, femur BMD, lumbar BMD, and femoral neck BMD compared with CHD patients (all P < 0.05). SDH patients also had lower anti‐osteogenic and inflammatory biomarkers, including FGF23, sclerostin, TNF, IL‐18, IL‐17a, and C‐reactive peptide (all P < 0.05). CHD modality was demonstrated to be a risk factor for low BMD (odds ratio: 4.02; 95% CI: 1.59-10.2, P = 0.003). In terms of skeletal muscle function, SDH patients had significantly higher 6‐minute walking test (444.6 vs. 424.9 m, P = 0.04) and higher fat‐free mass (52.3 vs. 51.68 kg, P = 0.02) compared with CHD patients. Higher fat‐free mass and handgrip strength were associated with a 34% and 23% lower risk of low BMD, respectively. SDH patients had lower levels of the uremic toxin asymmetric dimethyl‐l‐arginine (ADMA) (1.8 vs. 2.07 μM, P = 0.002) and fasting blood glucose (132.6 vs. 141.7 mg/dL, P < 0.02) than CHD group. SDH patients also displayed higher levels of haemoglobin when compared with CHD group (11.9 vs. 10.2 g/dL, P < 0.0001). Conclusions The present study improves our understanding of the relationship between dialysis modality and clinical variables that may influence HD patient's health. Grip strength and lean mass were positively correlated with bone mineral density in HD patients regardless of dialysis modality. SDH was associated with better bone mineral density, inflammatory profile, and skeletal muscle function when compared with CHD patients. These findings provide more evidence of the clinical benefits of SDH that should be explored in greater detail.